Cell biology and histology - Gartner, Leslie P.; Hiatt, James L.; Strum, Judy M. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"BRS Cell Biology and Histology is an outline-format review for USMLE and course exams, with review questions at the end of each chapter and a comprehensive USMLE-format examination at the end of the book. Each chapter also features a high-yield section on clinical correlations. The book is concise and well illustrated, with line drawings and electron micrographs"--Provided by publisher.
Includes index.
Keywords: Histology -- Outlines, syllabi, etc; Cytology -- Outlines, syllabi, etc; Histological Techniques -- Outlines; Cytological Techniques -- Outlines